2018
DOI: 10.1088/1361-6404/aaabc7
|View full text |Cite
|
Sign up to set email alerts
|

Stokes versus Basset: comparison of forces governing motion of small bodies with high acceleration

Abstract: In this paper, the importance of the forces governing the motion of a millimetre-sized sphere in a viscous fluid has been examined. As has been shown previously, for spheres moving with a high initial acceleration, the Basset history force should be used, as well as the commonly used Stokes force. This paper introduces the concept of history forces, which are almost unknown to students despite their interesting mathematical structure and physical meaning, and shows the implementation of simple and efficient nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…As shown in figure 5, when the particle is close to the collector centre, the capillary force F C and the drag force F D are the dominant forces, the Basset force F B takes the third place, and the resultant of force by the pressure gradient and the added mass force by liquid flow F PA is the smallest force, which is negligible as compared with the former three forces. The large value of F C reached is rational owing to the decreasing distance between the particle and the collector; F D is large owing to the large velocity difference between the fluid and the particle caused by the large capillary force; and the observed order of importance F D > F B > F PA is similar to that of Krafcik et al [47]. When the particle is far away from the collector, the capillary force effect is very weak, the particle follows the streamline (a typical particle motion at low Stokes numbers [34]) and the drag force is little.…”
Section: Resultssupporting
confidence: 72%
“…As shown in figure 5, when the particle is close to the collector centre, the capillary force F C and the drag force F D are the dominant forces, the Basset force F B takes the third place, and the resultant of force by the pressure gradient and the added mass force by liquid flow F PA is the smallest force, which is negligible as compared with the former three forces. The large value of F C reached is rational owing to the decreasing distance between the particle and the collector; F D is large owing to the large velocity difference between the fluid and the particle caused by the large capillary force; and the observed order of importance F D > F B > F PA is similar to that of Krafcik et al [47]. When the particle is far away from the collector, the capillary force effect is very weak, the particle follows the streamline (a typical particle motion at low Stokes numbers [34]) and the drag force is little.…”
Section: Resultssupporting
confidence: 72%
“…The Maxey-Riley equation (1) or its dimensionless form ( 5) is an integro-differential equation, which means that during the integration process in each time step it is necessary to compute the Basset history force integral term. For this purpose we used variable time step order one quadrature scheme presented in [36] proposed in [25]. In this sense, the Maxey-Riley equation ( 5) can be transcribed to the system of ordinary differential equations (ODEs).…”
Section: Numerical Integration Of the Maxey-riley Equationmentioning
confidence: 99%
“…Because of the difficulties associated with calculating the integral term, Basset hereditary force is often ignored. However, in a number of studies, it is shown that Basset hereditary force could influence the bubble dynamics. An integral/quadrature scheme has been developed for the numerical estimation of the Basset hereditary force …”
Section: Introductionmentioning
confidence: 99%